Determination of the siltation volume of riverbed reservoirs - Akhmedkhodjaeva I.A (Peerian Journals Publishing, 2023)
For the Republic of Uzbekistan, assessing the degree of siltation of reservoirs is of paramount importance; it is important to take into account changes in the process of siltation in the past and trends in its future changes when planning and managing water resources. The article presents a methodology for calculating the volume of siltation in riverbed reservoirs located on the territory of the Republic of Uzbekistan. The dependence of the intensity of siltation of riverbed reservoirs on their geographical location and reduced turbidity was obtained. The forecast of siltation of the reservoir was made based on a comparison of design characteristics taking into account the stage of siltation of the reservoir at the time of the estimated time.
Keywords: reservoir; volume; reservoir siltation